2011
DOI: 10.1080/17429145.2011.641229
|View full text |Cite
|
Sign up to set email alerts
|

Variability of nitrogen uptake and assimilation among N-efficient and N-inefficient wheat (Triticum aestivumL.) genotypes

Abstract: Ten genotypes of wheat (Triticum aestivum L.) were grown for 20 days in complete nutrient solution with 1 mM (nitrogen-insufficient), 4 mM (nitrogen-moderate) and 10 mM (nitrogen-sufficient) nitrogen (N) levels, and nitrogen efficiency (NE) was analyzed. Of these 10 genotypes, VL829 was identified as the most N-efficient, while HUW234 the most N-inefficient. To find out the physiological basis of this difference, we investigated the possible role of NO 2À 3 influx across the root cell plasma membrane in confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Hakeem et al (2012) reported that high NUE genotypes showed more NR activity and consistent even with increase in N levels where as NR activity was increased with increase in N levels in low NUE genotypes. High NUE genotypes have low threshold level for NR activity and hence there was no change in NR activity with increase in N levels (Anjana et al, 2007;Chandna et al, 2012).…”
Section: Nr Activitymentioning
confidence: 99%
“…Hakeem et al (2012) reported that high NUE genotypes showed more NR activity and consistent even with increase in N levels where as NR activity was increased with increase in N levels in low NUE genotypes. High NUE genotypes have low threshold level for NR activity and hence there was no change in NR activity with increase in N levels (Anjana et al, 2007;Chandna et al, 2012).…”
Section: Nr Activitymentioning
confidence: 99%
“…Plants allocate new biomass to the organs used for acquiring the scarce resources to adjust the ionic imbalance (Marschner 1995 ). Many studies have focused on the relationships between nutrition, plant growth, and development and have explained the mechanisms of ion transport and the biochemical pathways infl uenced by mineral scarcity (Hermans et al 2006 ;Chandna et al 2012 ;Hakeem et al 2012a , b ). Although understanding about the molecular and physiological processes involved in sensing, signaling, and allocation of defi cient nutrients is poor, but with onset of microarray technologies to study gene expression, study of transcriptional changes associated with mineral imbalance has become easier (Hammond et al 2004 ).…”
Section: Signaling and P Defi Ciencymentioning
confidence: 99%
“…The biochemical parameters associated with internal N assimilation affect the N physiological efficiency in plants and N storage in grains (Chandna et al, 2012;Zhang et al, 2015). The activities of NR, NIR, and GS, the critical enzymes involving internal N assimilation efficiency, regulate the NUE behaviors of plants (Oaks, 1994;Truax et al, 1994;Esen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%